2016
DOI: 10.1080/14767058.2016.1256993
|View full text |Cite
|
Sign up to set email alerts
|

Deceleration area and fetal acidemia

Abstract: Total deceleration area showed the greatest predictive ability for fetal acidemia and its measure could help to estimate intrapartum fetal acid-base status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 30 publications
(32 reference statements)
3
29
0
Order By: Relevance
“…This result has already been observed in the literature [8] [14] Open Journal of Obstetrics and Gynecology [15]. Indeed, a Spanish case-control study demonstrated that decelerations occurring during the last 30 minutes of labor were the best marker of neonatal acidosis [14].…”
Section: Discussionsupporting
confidence: 73%
“…This result has already been observed in the literature [8] [14] Open Journal of Obstetrics and Gynecology [15]. Indeed, a Spanish case-control study demonstrated that decelerations occurring during the last 30 minutes of labor were the best marker of neonatal acidosis [14].…”
Section: Discussionsupporting
confidence: 73%
“…Graham et al also showed that total deceleration area (calculated with the same equation as in the study by Cahill) during the last 30 and 60 min differed significantly between a group of acidemic fetuses with encephalopathy and a control group . Furthermore, Marti et al studied the relation between total deceleration area during the last 30 min of labor and found a significant relation to fetal acidemia . However, to be able to use deceleration area as a parameter measured continuously during labor, a computerized method for assessment is needed.…”
Section: Discussionmentioning
confidence: 99%
“…The calculation of deceleration area was manual and complex. Several more recent studies have pointed out deceleration area as an important predictor of neonatal acidemia . Many of these studies have used an approximation of deceleration area as deceleration (width × depth)/2 .…”
Section: Introductionmentioning
confidence: 99%
“…32 A recently published case-control study of 204 infants also found that deceleration area was the superior feature to identify infants with acidemia. 33 These led us to hypothesize that deceleration area might be an important predictor of acidemia and morbidity within a large, modern, and unselected cohort. Additionally, the predictive value of tachycardia within our study remains consistent with findings from animal studies, which suggests that with labor-like cord occlusions there is an increase in the magnitude and slope of the fetal heart rate.…”
Section: Commentmentioning
confidence: 99%